2010
DOI: 10.4071/isom-2010-ta1-paper2
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Demonstration of TSV Interconnects and Multilevel Metallization for 3D Si Interposer Applications

Abstract: A TSV test vehicle lot and 3D interposer demonstration lot were successfully fabricated and tested. Fabrication of the TSV test vehicle was accomplished using three process (mask) levels – front-side metal, backside TSV, and backside metal. The TSVs were formed using a vias-last approach with a nominal TSV size of 100μm, and an aspect ratio of 6:1. DRIE bottom clear process conditions were tested which produced 100 % yield on TSV contact chains with up to 540 vias. In addition, optimum process conditions resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…As bottom clear etch time was increased, the TSV chains yield improved, but the isolation resistance decreased. This suggested that etching too long can result in loss of passivation at the via sidewalls and illustrates the need to carefully optimize the etch conditions for this key step [6]. For the full interposer wafers, electrical testing of the MLM layers showed up to 100% yield on 4-layer test chain structures which included 26,400 vias each.…”
Section: A Tsvs Last Back-side Unfilled Vias Processmentioning
confidence: 98%
See 4 more Smart Citations
“…As bottom clear etch time was increased, the TSV chains yield improved, but the isolation resistance decreased. This suggested that etching too long can result in loss of passivation at the via sidewalls and illustrates the need to carefully optimize the etch conditions for this key step [6]. For the full interposer wafers, electrical testing of the MLM layers showed up to 100% yield on 4-layer test chain structures which included 26,400 vias each.…”
Section: A Tsvs Last Back-side Unfilled Vias Processmentioning
confidence: 98%
“…The average measured contact resistance was 4mȍ for the dual damascene levels. [6] Thermal cycling of the TSV electrical test wafers showed no TSV via chain yield loss for up to three reflow cycles at 225ºC. A slight increase in 4-wire TSV resistance was observed, with a measured change of about 0.6 mȍ per reflow cycle [6].…”
Section: A Tsvs Last Back-side Unfilled Vias Processmentioning
confidence: 98%
See 3 more Smart Citations